Faster movement in nonhabitat matrix promotes range shifts in heterogeneous landscapes. Issue 7 (14th May 2019) - Crone, Elizabeth E.; Brown, Leone M.; Hodgson, Jenny A.; Lutscher, Frithjof; Schultz, Cheryl B.
Abstract: Ecologists often assume that range expansion will be fastest in landscapes composed entirely of the highest‐quality habitat. Theoretical models, however, show that range expansion depends on both habitat quality and habitat‐specific movement rates. Using data from 78 species in 70 studies, we find that animals typically have faster movement through lower‐quality environments (73% of published cases). Therefore, if we want to manage landscapes for range expansion, there is a trade‐off between promoting movement with nonhostile matrix, and promoting population growth with high‐quality habitat. We illustrate how this trade‐off plays out with the use of an exemplar species, the Baltimore checkerspot butterfly. For this species, we calculate that the expected rate of range expansion is fastest in landscapes with 15% high‐quality habitat. Behavioral responses to nonhabitat matrix have often been documented in animal populations, but rarely included in empirical predictions of range expansion. Considering movement behavior could change land‐planning priorities from focus on high‐quality habitat only to integrating high‐ and low‐quality land cover types, and evaluating the costs and benefits of different matrix land covers for range expansion.